Causal relationsships in a simple sentence. (Eurasian Journal of Philology Science and Education, 2015)
The given article is devoted to the analyses of prepositional word-combinations in German language, expressing causal relations. Deferent semantic variants of causality expressed by prepositional word-combinations are considered in the article. In this paper we attempted to identify the means of expression category of causality and functional features in a simple sentence. In German simple sentence means expression of cause and effect are the morfological means individual tokens, compound words, prepositional-declensional design. Internal causal link, namely the internal emotional state of the people, the psychic activity of man is expressed through substantive andadjectival composite. The objective nature of the causal relationship express complex words preposition combination with the preposition von. Causal connection of logical character explicated by tokens, substantive and adjectival composite and prepositional phrases aus, vor, wegen, aufgrund. The analyses of prepositional word-combinations, causal relations, deferent semantic variants of causality, prepositional word-combinations. The objective nature of the causal relationship is causal connection of logical character.
Keywords: causal relations; word-combinations; category of causality and functional features; the objective nature of the causal relationship; causal connection of logical character